Frailty and outcomes in octogenarians with atrial fibrillation treated with edoxaban: ESCAPE study. (3rd October 2022) - Denas, G; Zoppellaro, G; Granziera, S; Pagliani, L; Iliceto, S; Pengo, V
Abstract: Background: Frailty is associated with significant morbidity and mortality among elderly adults. Whether frailty predicts adverse outcomes in patients treated with oral anticoagulants for stroke prevention in atrial fibrillation remains uncertain. Purpose: To examine the impact of frailty in clinical outcomes in elderly patients with non-valvular atrial fibrillation treated with edoxaban. Methods: This is an observational prospective single centre cohort study enrolling consecutive naïve to anticoagulation patients of age ≥80 years starting oral anticoagulation with edoxaban for stroke prevention in non-valvular atrial fibrillation and followed up for 2 years. At baseline, all patients were evaluated for frailty, comorbidities, medications, and stroke and bleeding risk factors. Frailty was assessed using the Survey of Health Ageing and Retirement in Europe Frailty Index (SHARE-FI) tool, a validated frailty measure centred on health resource utilisation, with the cohort stratified into non-frail, pre-frail and frail. The clinical outcomes were the cumulative incidence of stroke/systemic embolism, major bleeding, and clinically relevant non-major bleeding (CRNMB), and individual components part of the composite outcome. Results: Among 160 patients who received edoxaban for stroke prevention in atrial fibrillation, 34% were frail, 20% pre-frail, 46% non-frail. The mean age of the cohort was 85±4 years and 58% were female. The mean CHA2DS2VASc score was 4±1. Mean Cockroft-Gault creatinine clearance (CrCl) was 52±17 mL/min, and edoxaban 30mg was administered to 59% of patients as per indications (weight ≤60 kg and/or, CrCl 15–50 ml/min). The follow up extended for 681±289 days. Primary endpoint occurred in 46 patients (28.7%; annualised rate 15.4%patient-years): 19 events occurred in non-frail, 9 in pre-frail, and 18 in frail patients (p=0.6). Stroke/systemic embolism occurred in 2.2%, major bleeding in 5.0%, and CRNM bleeding in 10.0% of patients. Frailty was not a predictor of the events part of the composite outcome (non-frail 5.4% vs pre-frail 0% vs frail 1.9%, p=0.27; non-frail 5.4% vs pre-frail 9.4% vs frail 1.9%, p=0.29; and non-frail 13.5% vs pre-frail 3.1% vs frail 9.3%, p=0.25; for stroke/systemic embolism, major bleeding, and CRNMB, respectively). Cumulative rate of events (Figure) did not differ in frail versus the rest (non-frail and pre-frail) of patients (p=0.521). Conclusions: Frailty status was not a predictor of events among the elderly with atrial fibrillation treated with edoxaban. Anticoagulation with edoxaban is feasible in octogenarians even if frail. Funding Acknowledgement: Type of funding sources: None.